The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jcp.2017.07.041
|View full text |Cite
|
Sign up to set email alerts
|

CVD-MPFA full pressure support, coupled unstructured discrete fracture–matrix Darcy-flux approximations

Abstract: Two novel control-volume methods are presented for flow in fractured media, and involve coupling the controlvolume distributed multi-point flux approximation (CVD-MPFA) constructed with full pressure support (FPS), to two types of discrete fracture-matrix approximation for simulation on unstructured grids; (i) involving hybrid grids and (ii) a lower dimensional fracture model. Flow is governed by Darcy's law together with mass conservation both in the matrix and the fractures, where large discontinuities in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Our convergence ratios and errors magnitude are very close to those presented by Ahmed et al, 20 as shown in Figure 7, despite the errors magnitude, for = 1, of both CVD-MPFA versions (TPS and FPS) being slightly lower than those of the MPFA-D. Otherwise, for the other values of (for all values of a) the errors magnitude obtained by the MPFA-D are basically the same and never bigger than those of the CVD-MPFA (Figure 7).…”
Section: F I G U R Esupporting
confidence: 91%
See 4 more Smart Citations
“…Our convergence ratios and errors magnitude are very close to those presented by Ahmed et al, 20 as shown in Figure 7, despite the errors magnitude, for = 1, of both CVD-MPFA versions (TPS and FPS) being slightly lower than those of the MPFA-D. Otherwise, for the other values of (for all values of a) the errors magnitude obtained by the MPFA-D are basically the same and never bigger than those of the CVD-MPFA (Figure 7).…”
Section: F I G U R Esupporting
confidence: 91%
“…In the convergence test, the proposed formulation performed very well when compared to the CVD-MPFA, method that has been recently adapted in the Hybrid-Grid context, 20 being capable to return similar error magnitudes and equivalent convergence rates.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations